Blowin’ in the wind: Onshore winds drive the occurrence of bluebottles (Physalia spp.) at east Australian beaches - Daniel E. Hewitt; Amandine Schaeffer; Jasmin C. Lawes; Sean Kelly; Alistair G.B. Poore; Moninya Roughan; Saima Ajaz; Timothy C. Ingleton; Kylie A. Pitt (Ocean & Coastal Management, 2026)

The New South Wales nearshore wave tool – an interactive platform integrating high-resolution wave data for enhanced coastal science and management - Thomas B. Doyle; Andrew Bradford; Sean Garber; Raimundo Ibaceta; Bradley D. Morris; Michael A. Kinsela; Timothy C. Ingleton; Iman Jizan; David Taylor; David J. Hanslow; Kym Bilham (Environmental Modelling & Software, 2025)

Quantifying the effects of extreme flooding on coastal reef fishes - Matthew J. Rees; Nathan A. Knott; David Harasti; Timothy C. Ingleton; Hamish A. Malcolm; Rachel Przeslawski (Ecology, 2025)
The ecological impacts of extreme floods to benthic ecosystems in oceanic environments remain unclear, as events are difficult to observe and quantify. Between 2020 and 2022, an unusually long La Niña resulted in substantial flooding across southeastern Australia. Major floods in the Hawkesbury‐Nepean River led to an unprecedented flood plume extending ~70 km offshore to depths of ~50 m, exposing coastal biodiversity to rare environmental conditions. Here, we use long‐term monitoring data to quantify the impacts of large‐scale flooding to coastal rocky reef fishes. Flooding reduced the total abundance and species richness of reef fishes by 50% and 13%, respectively. Declines were primarily due to reductions in the abundance of planktivores (−75%) and benthic invertivores (−40%). Assemblages at reference locations isolated from large rivers were stable across the study period, indicating observed patterns were in response to floods. Surveys 1‐year post flooding signaled that benthic invertivores were beginning to recover but not planktivores. Our results demonstrate the detrimental impacts of extreme flooding to some coastal rocky reef fishes. Given projected increases in the severity and frequency of rainfall due to climate change, our findings suggest that extreme flooding may compromise ecosystem functions and services provided by rocky reef fish in a future climate.